Time-Driven Activity Based Costing jako narzędzie zarządzania zasobami przedsiębiorstwa - Putyra, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents a new approach to activity based costing Time Driven Activity Based Costing. A new method, using opportunities of IT development, allows to allocate costs of resources to cost objects more precisely. Moreover it is a very useful tool concerning long-term resource planning and capacity management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 363-375